Ablution Socks: The Logic of Market Capitalism and Its Limits - GhaneaBassiri, Kambiz (MAVCOR journal, 2022)
The marketing of “wudhu socks" provides an interesting window onto how the forces of consumer capitalism in twenty-first-century America are brought to bear on a centuries-old hermeneutical, legal, and theological tradition in Islam that has long conceptualized purity through embodiment and objects.